1998
DOI: 10.1351/pac199870101881
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and molecular state of C60 and C70 in solvents and solvent mixtures

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 0 publications
1
53
0
Order By: Relevance
“…[9][10][11][12][13][14][31][32][33][34][35] The state of fullerenes, either molecular or colloidal, in the so-called 'good' or 'strong' solvents, such as CS 2 , toluene, and benzene, is still a matter of discussion. 8,10,11,14,[36][37][38][39][40] Some authors believe that in such a case, aggregates appear only as a result of sonication. 11 The aggregates (if any) in 'good' solvents are unstable, destroyed by hand-shaking, 8 and their formation may be (partly) caused by interaction with oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][31][32][33][34][35] The state of fullerenes, either molecular or colloidal, in the so-called 'good' or 'strong' solvents, such as CS 2 , toluene, and benzene, is still a matter of discussion. 8,10,11,14,[36][37][38][39][40] Some authors believe that in such a case, aggregates appear only as a result of sonication. 11 The aggregates (if any) in 'good' solvents are unstable, destroyed by hand-shaking, 8 and their formation may be (partly) caused by interaction with oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the solubility of fullerenes are of importance for the development of methods for chromatographic and prechromatographic (based on solubility and extraction equilibria) separation of industrial fullerene mixtures and for studies of chemical reactions with the participation of fullerenes [1][2][3][4][5][6][7]. There are ample experimental data on the solubility of pure light ( ë 60 and ë 70 ) fullerenes in various inorganic and diverse organic solvents (alkanes, aromatic solvents, alcohol, carboxylic acids, ionic liquids, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the authors of [11] observed three solid phases and two eutonic points in the ë 60 -ë 70 -1,2 -dimethylbenzene system with the formation of two three-phase fields in the phase diagram. At 298 K, solid solution was based on ë 60 · 2( Ó -ë 6 ç 4 (ëç 3 Note that the importance of studying the solubility of fullerenes in styrene is largely determined by the possibility of the optimization of thermocatalytic styrene polymerization conditions for the production of polystyrene modified with fullerenes with unique service characteristics [12,13]. The isothermal solubility in the ë 60 -ë 70 -styrene system at 25°ë was studied by the isothermal saturation method.…”
Section: Introductionmentioning
confidence: 99%
“…We chose toluene as the reacting solvent because of its relative high capacity to dissolve fullerenes. 9) MeL (final concentration 600 mM) containing an antioxidant (final concentration 0.60 mM for C 60 and C 70 , and 0.060 mM for -tocopherol) was dissolved in toluene. To this was added AMVN (final concentration 6.0 mM), and this was incubated at 37 C with mechanical shaking.…”
mentioning
confidence: 99%